Green Commute: Reducing Carbon Footprint in Commuting Scenarios in Karaj - Shima Oveisi; Mazaher Moeinaddini (Sustainable Earth Trends)
This study addresses the substantial contribution of mobile sources in commuting to greenhouse gas (GHG) emissions in megacities and underscores strategies for carbon footprint emission reduction. Field interviews and questionnaires facilitate data collection, enabling the classification of the studied vehicle fleet based on various parameters. The scenarios aim to minimize GHGs from the commute, utilizing the International Vehicle Emission (IVE) model to establish a primary carbon footprint emission inventory for commuting in Karaj. The base scenario reveals that commuting in Karaj produces 1579423 grams of CO2e, with CO2, N2O, and CH4 emissions at 1389039 grams, 43.74 grams, and 6385.38 grams, respectively. Three carbon footprint reduction scenarios, involving removing diesel vehicles, adopting natural gas-fueled vehicles, and replacing Euro 4 and 5 with older vehicles, demonstrate that the removal of diesel vehicles (S1) and adopting natural gas-fueled vehicles, and replacing Euro 4 and 5 with older vehicles (S3) are the most effective strategies, achieving a 99% efficiency rate in reducing CO2e. This study highlights the substantial impact of curbing carbon emissions from GHGs. S1 and S3 show significant reductions in carbon footprint emissions, emphasizing the crucial role of strategic planning and greenhouse gas minimization in controlling emissions from commuting. These findings underscore the critical importance of reducing carbon footprints and commuting to effectively mitigate GHGs in congested urban areas.